What is wellness? The role of human values. (December 2020) - Crowe, Jonathan
There is a growing literature on wellness for law in Australia and elsewhere. Significant uncertainty exists, however, about what exactly wellness means in this context. I argue that wellness is not best understood either as the absence of psychological distress or as the presence of life satisfaction or positive affect. I propose an alternative understanding of wellness that centres around the role of basic values in human flourishing. Wellness, I suggest, consists in participating in the various dimensions of human flourishing in a balanced and integrated way. This approach draws out the deep challenges that wellness poses to legal education and practice.